Removal of diclofenac by three-dimensional electro-Fenton-persulfate (3D electro-Fenton-PS). (March 2019) - Long, Yingying; Feng, Yan; Li, Xue; Suo, Ning; Chen, Hao; Wang, Zhongwei; Yu, Yanzhen
Abstract: Diclofenac (DIC) is a new type of contaminant that has been widely detected in the water environment, posing threats to the ecological environment and human health. However, the conventional wastewater treatment process has a very limited ability to reduce DIC. In this research, persulfate is added to electro-Fenton with the three-dimensional particle electrode (TDE) process whose particle electrodes were formed from manganese slag with loaded active substance (Cu: Fe = 1:1) to construct a three-dimensional electro-Fenton-persulfate (3D electro-Fenton-PS) process to investigate the removal rate of DIC under the optimum working conditions. The effects of different persulfate addition, activator addition and different activators on the removal rate of DIC were researched, respectively. The removal rate of DIC reached 96.3% when the persulfate and the Fe 0 addition were 1.50 mM and 3.00 mM, respectively. The results showed that and OH existed simultaneously in the reaction system, and the removal of DIC was the result of the two free radicals. Moreover, degradation pathways and mechanism of DIC were also discussed. The study may provide a new theoretical basis and technical support for the treatment of DIC in municipal wastewater. Highlights: 3D electro-Fenton-PS reactor could effectively remove DIC. Fe 0 was more suitable as an activator of persulfate than Fe 2+ . The removal of DIC was the result of a combination of and OH. The degradation pathways of DIC probably were decarboxylation and dechlorination.